Bone Tissue Response to Plasma Sprayed Hydroxyapatite Coatings: An In Vivo Study on Rabbit Femoral Condyles: Bone tissue response to hydroxyapatite-coated Ti-6Al-4V substrates - Behnamghader, Aliasghar; Sharifi, Davood; Soroori, Sarang; Bagheri, Narjes; Tolouei, Ranna; Nemati, Roghieh; Najjar, Denis; Iost, Alain (Iranian Journal of Pharmaceutical Sciences, 2008)
In this study, hydroxyapatite was coated on titanium substrates by plasma spraying process. A well-known porous and lamellar microstructure was found in the lateral and outer surface of coating. The phase composition was studied by XRD and the morphological and the microstructural aspects were investigated by scanning electron and optical microscopy. The hardness of coatings and substrates was measured by Vickers indentation method. For in vivo study, rabbit condyles were exposed to two groups of coated and uncoated samples. Radiographyically, different parameters such as bone lysis, sclerosis, displacement of samples and bone resorption were taken into consideration and no statistically differences between the two groups, with no sign of infection on the edges of each hole were found. Histopathological interpretation of all coated samples indicated that the extent of callus and thickness of speculae were quite distinct from that of uncoated group. In this group, the space between implant and canal was filled up with matured connective tissues and plenty of bone speculae of woven bone in nature. However, these speculaes were thinner and immature as compared to coated samples.